Go-Tour Based Semarapura-Bali City Tour Package Model - Pracintya, Ida Ayu Etsa; Oktaviani, Putu Eni; Prawira, Putu Agung Surya (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Klungkung is one of the smallest regencies in Bali, but has tourism potential to be developed. Historically, Klungkung was a very famous kingdom led by a king. In the colonial era, the Klungkung Kingdom experienced an event called the Puputan War. The event left a historical building called Kertagosa. Kertagosa consists of Balai Kertagosa, Balai Kambang (Gili Park), Pemedal Agung, Semarajaya Museum. Klungkung has an important value to the history of Bali, so it needs to be maintained and preserved. This is reinforced by Law No. 11 of 2010. Therefore, this study focuses on the development of tour packages in Klungkung through smart tourism based on go-tour. The research method used was a qualitative method with data analysis techniques using descriptive-qualitative analysis techniques with Efas, Ifas, and SWOT analysis. The results of this study showed that the strategy and model for developing city tour packages through the Go-Tour feature can be applied to support tourism activities in Semarapura City.